Samuel Bowles. Planning Educational Systems for Economic Growth. Harvard Economic Studies no. 33, Cambridge, Harvard University Press, 1969. 245 p. - Barkin, David (El Colegio de México A.C., 1971)
SAMUEL BOWLES, Planning Educational Systems for Economic Growth. Harvard Economic Studies No. 33, Cambridge, Harvard University Press, 1969.